RELATIONSHIP between NURSE CHARACTERISTICS WITH DISCHARGE PLANNING IMPLEMENTATION - Ana Zakiyah; Duwi Basuki; windu santoso (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Discharge planning is one of the activities in the provision of nursing care on patients in the hospital, it will have a shortening impact on patient care in the hospital and reduce the patient's recurrence rate, but the implementation is not appropriate. so far, implementation of Discharge planning is still to be done after the patient finished having treatment by making a summary of the recording of patients return. Various characteristic factors of nurses can influence the implementation of discharge planning in hospital. The research purpose was to know the relationship of factors that influence discharge planning with the implementation of discharge planning. The research design used was cross-sectional, the instrument used was the questionnaire about the characteristics of the nurses and the implementation of discharge planning. The population of research was nurses who served in the inpatient room RSI Sakinah Mojokerto number of 80 nurses and obtained the number of 67 samples with proportional random sampling technique. The result of analysis with pearson correlation for age, education, length of work and chi-square for marital status showed that the characteristics of nurses related to discharge planning implementation were educational factor with p-value 0,023. The higher the nurse education caused more critical, logical and systematic in thinking so as to improve the quality of its work and the greater the desire to utilize the knowledge and skills it possesses keywords : discharge planning, nurses, education